EDUKASI MEMBUKA KESUKSESAN PERAN PROFESIONALISME DAN ETIKA DALAM BEKERJA - Hamdani, Ibnu Mansyur; Bustamin, Syamsumar (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Providing education regarding the role of professionalism and ethics in achieving career success, especially for students. Professionalism and ethics play a crucial role in preparing students to enter the world of work successfully. Professionalism is defined as attitudes, behaviors and skills that reflect competence, responsibility, integrity and cooperation in the work environment. Meanwhile, ethics refers to the moral principles that govern behavior and interactions in the workplace. Important aspects of professionalism and ethics at work. First, professionalism involves maintaining integrity by demonstrating honesty, consistency, and respecting the professional code of ethics. Second, responsibility is a key factor in career success, including respecting deadlines, respecting obligations to work, clients, or teams. Third, cooperation is an important skill in achieving career success, including the ability to work in teams, listen, and communicate well. Several ethical aspects at work, respecting privacy and confidentiality, avoiding conflicts of interest, complying with laws and regulations, avoiding discriminatory behavior, and providing high quality services are ethical principles that need attention. By understanding the role of professionalism and ethics in work, students will be able to prepare themselves well to face challenges and achieve their career goals. By adopting good professional and ethical attitudes, they can build a good reputation, earn the trust of others, and expand their professional network.